Domesticating a Marian Apparition and Pilgrimage Site: A Case of Mount Živčák in Slovakia - Bahna, Vladimír (Numen, 2025)
This article covers the development of a Marian apparition and pilgrimage site called Mount Živčák, located near Turzovka in northwest Slovakia. Since its inception in 1958, the site has undergone shifts in status, social function, and ritual behavior, culminating in its domestication by the Catholic Church. A transition of the church’s attitude from an official and long-lasting rejection to active support and full-time management was followed by changes in the forms of religiosity expressed by pilgrims. The initial spontaneous forms of vernacular Christianity were expelled from the main ritual practice and replaced by the official Catholic liturgy. Although the site has become fully organizationally embraced, the apparitions remain unconfirmed. This development is put into the context of theories about apparitions and pilgrimage with a particular focus on the interaction between vernacular and institutionalized religion.